IMPLEMENTATION OF CHARACTER EDUCATION IN THE MERDEKA CURRICULUM - Irnawanto, Fauzi; Yayuk, Erna; Kuncahyono, Kuncahyono (JURNAL EDUSCIENCE, 2025)
Purpose-This study aims to examine the implementation of character education in the Merdeka Curriculum, focusing on planning, implementation, and evaluation in vocational school environments. This study is motivated by the decline in morals of the younger generation, which is marked by increasing juvenile delinquency, lack of discipline, and increasing social challenges in the digital era.Methodology-This study uses a qualitative descriptive approach with a purposive sampling design. The subjects of the study included the principal, vice principal, subject teachers, and grade XI students. Data collection techniques were done through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman interactive model, consisting of data collection, reduction, presentation, and conclusion.Findings-The study results indicate that character education is systematically integrated into school policies, vision, mission, and curriculum. Implementation is carried out through experiential learning, extracurricular activities such as the Muhammadiyah Student Association (IPM) and Tapak Suci, and routine practices such as Al-Qur'an recitation, congregational prayer, morning exercise, the "Clean Friday" program, and social activities. Evaluation is carried out through direct observation, character journals, and periodic review meetings. These findings confirm the active role of these practices in shaping students' character.Significance-This study contributes to understanding how vocational schools contextualize character education in national curriculum reform. This study emphasizes increasing teacher involvement and parental participation to strengthen students' character development.